Students' Algebraic Thinking in Using the Geogebra Application - Masnia, Masnia; Habibie, Zulqoidi R (Universitas Islam Sultan Agung, 2023)
Algebra is knowledge in education. The ability to think should be known so that it can be maximized in the learning process, one of which is the ability to think in algebra. In the process of working on various algebra problems, students carry out generational activities, transformation activities, and global meta-level activities. Learning algebra will be easy if combined with technology. One of the technologies that can support algebra learning is Geogebra. The research aims to determine how students' algebraic thinking abilities use the Geogebra application. The method in this research is qualitative, with a case study type. The research subjects were students taking calculus courses in the Informatics Engineering study program at a private campus in Jakarta. The research results show that the algebraic thinking ability levels consist of high, medium, and low. High algebraic thinking abilities have high generational, transformational, and global meta-level abilities, while moderate algebraic abilities have moderate generational abilities; transformational abilities tend to be medium to high, and global meta-level abilities tend to be medium to low. Low levels of algebraic thinking ability tend to have moderate to low generational abilities, low transformational abilities, and low global meta-level abilities.